Prospect and Challenges of Federal Government in Nepal (Shahid Kirti Multidisciplinary Journal, 2026)
The study discusses the opportunities and challenges of the federal governance in Nepal in the local level following the 2015 Constitution adoption. The paper is based on the theory of cooperative federalism and decentralization and the case study approach of the study pertains to the Dhankuta Municipality area using the qualitative method. The primary data was gathered in the form of semi-structured in-depth interviews with elected officials, administrative employees, and service providers and supplemented by field observations. The result shows that federal restructuring has enhanced accessibility of services, responsiveness of the locality, participatory planning, social inclusion, and grassroots resolution of conflicts. These positive effects are, however, limited by ambiguity in the law and policy, fiscal dependency, poor intergovernmental coordination and lack of human and technical capacity locally. This paper concludes that the institutional form of the federalism of Nepal is still transitional, and its effective consolidation further needs a better legal enforcement, economic separation, capacity building, and enhanced collaboration systems among various levels of government.